WIRELESS SENSOR NETWORK BASED SMART HOME SYSTEM WITH SERVICE ROBOT - D.D.Ahirrao; B.R.Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper is concerned with constructing a prototype intelligent home environment for home service robot. In this environment, multi-pattern information can be represented by some intelligent artificial marks. Light-packs service robots can provide reliable and intelligent service by interacting with the environment through the wireless sensor networks. The intelligent space consists the following main components: smart devices with intelligent artificial mark; home server that connects the smart device and maintains the information through wireless sensor network; and the service robot that perform tasks in collaboration with the environment. In this paper, the multi-pattern information model is built, the construction of wireless sensor networks is presented, and the smart and agilely home service is introduced. Finally, the future direction of intelligent space system is discussed.